Collecting plant genetic diversity: technical guidelines. 2011 update - Guarino, Luigi; Ramanatha Rao, V.; Goldberg, E.; Bioversity International (2011)
This resource guides new and experienced collectors on how to sample, collect and preserve a wealth of genetic resources – not only crop plants and trees but also wild species, symbiotic bacteria and fungi, pollen and even DNA.